OBSERVASI SEBAGAI ALAT EVALUASI DALAM DUNIA PENDIDIKAN DAN PENGAJARAN - Sitti Mania (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2008)
Evaluation is one of the key factors in the field of education, particularly in the process of teaching, due to its function to assess the extent to which the development of students. In practice, evaluation may be done by using test and non-test technique. Observation, the central issue of this paper, is classified as non-test technique. It is an instrument of collecting data by a systematic process of surveillance and note taking on the behavior of students, both individually and collectively. Additionally, observation is considered the most relevant evaluation instrument to access the affective and psychomotor domain of students. One may implement participative, non-participative, and quasi observation. The quality of this instrument is judged based on its validity, which strongly due to the skill, knowledge, and attitude of the observer.